Impact of shoulder internal rotation on ulnar nerve excursion and strain in embalmed cadavers. A pilot study. (14th March 2016) - Gugliotti, Mark; Futterman, Bennett; Ahrens, Thomas; Block, David; Brown, Lauren; Dagro, Micheal; Falesto, James; Lyon, Aliza
Abstract : Design: Laboratory study, repeated-measures design. Objective: To determine if the substitution of shoulder internal rotation for external rotation during the upper limb neurodynamic test (ULNT3 ) evokes a comparable ulnar nerve excursion and strain in embalmed cadavers. Shoulder external rotation is a primary movement component of the ULNT3 . It has been suggested that shoulder internal rotation may provide a similar load to the nervous system. There are no data to either support or negate this claim. Methods: Excursion and strain were measured in the ulnar nerve of six embalmed cadavers during the traditional ULNT3 and an experimental maneuver using shoulder internal rotation. Results: The total means±SD of excursion for the traditional and experimental maneuvers were 2·11±0·89 and 2·09±0·92 mm, respectively. The total means±SD of strain for the traditional and experimental maneuvers were 5·274±2·223 and 5·241±2·308%, respectively. A very strong correlation ( r = 0·98) was shown to exist between maneuvers and this relationship was determined to be significant ( P = 0·001). Discussion: The results of this study provide evidence that there is no appreciable difference in excursion or strain when substituting shoulder internal rotation for external rotation during the ULNT3. Patients who exhibit limitation of shoulder external rotation mobility may benefit from this substitution when presenting with signs of ulnar nerve pathodynamics. Further research involving patients will be needed to assess the validity of the experimental maneuver for clinical application.